Evaluation Of Construction Support Through Business Entities (Case Study: Terbanggi Besar - Kayu Agung Toll Road) - Rafly Farandi Firdaus (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to design user interface (UI/UX) on UML Class Diagram learning application, especially for students who want to explore UML class diagram, by applying User-Centered Design (UCD) Method. This method involves students as the main users of the application in order to understand their needs, preferences, and user experience in depth. The application interface design will be focused on ease of use, attractive aesthetics, and user data security. The development of this application is expected to help students in learning and exploring UML class diagrams.